The Interactional Architecture of the Language Classroom - Paul Seedhouse (Universitat Autònoma de Barcelona, 2010)
This article provides a summary of some of the key ideas of Seedhouse (2004). The study applies Conversation Analysis (CA) methodology to an extensive and varied database of language lessons from around the world and attempts to answer the question ‘How is L2 classroom interaction organised?’ The main thesis is that there is a reflexive relationship between pedagogy and interaction in the L2 classroom. This means that there is a two-way, mutually dependent relationship. Furthermore, this relationship is the foundation of the organisation of interaction in L2 classrooms. The omnipresent and unique feature of the L2 classroom is this reflexive relationship between pedagogy and interaction. So whoever is taking part in L2 classroom interaction and whatever the particular activity during which the interactants are speaking the L2, they are always displaying to one another their analyses of the current state of the evolving relationship between pedagogy and interaction and acting on the basis of these analyses. So interaction in the L2 classroom is based on the relationship between pedagogy and interaction. Interactants are constantly analysing this relationship and displaying their analyses in their talk. An example of data analysis is provided, including discussion of socially distributed cognition and learning.